Strategi Pengolahan Limbah Udang sebagai Olahan Makanan Ringan di Desa Bumi Dipasena, Lampung - Yuniarti, Rizka; Karo, Pelliyezer Karo; Darminiyanti, Darminiyanti (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2023)
This research aims to analyze the potential of shrimp waste as a lightly processed food in the village of Bumi Dipasena, Lampung. The research method used in this research is qualitative with a descriptive approach. The results of the study show that shrimp waste has the potential to provide added value to the surrounding economy, with the potential of reaching 600 kg in one month. Waste processing has received support from the Maritime Affairs and Fisheries Service of Tulang Bawang Regency with the help of more fantastic boxes. The strategy for utilizing shrimp waste is to utilize the strengths possessed by shrimp waste, namely: New Processed Products; Distinctive and delicious taste; Shrimp shell waste contains protein, calcium, and chitin; shelf life of shrimp shell waste products that can last a long time without preservatives. In addition to taking advantage of existing strengths, it is necessary to make efforts to minimize existing weaknesses, namely by: Establishing a lightly processed food production site in a strategic place; training and preparing human resources in the production process; establishing cooperation with parties that can support smooth production so that the availability of lightly processed food products and prices can continue to be competitive and sustainable.